Plasma RANKL levels are not associated with breast cancer risk in BRCA1 and BRCA2 mutation carriers - Zaman, Tasnim (Oncotarget, 2019)
BACKGROUND: Aberrant progesterone/receptor activator of nuclear factor κβ (RANK) signaling has been implicated in BRCA1 breast cancer development. Furthermore, lower circulating RANKL has been reported among women with a BRCA mutation compared to non-carriers; however, there have been no reports of plasma RANKL levels and subsequent breast cancer risk. We prospectively evaluated the relationship between plasma RANKL and breast cancer risk among women with a BRCA1 or BRCA2 mutation. METHODS: An enzyme-linked immunosorbent assay was used to quantify plasma RANKL levels in 184 BRCA mutation carriers. Women were stratified into high vs. low RANKL based on the median levels of the cohort (5.24 pg/ml). Kaplan-Meier survival analysis was used to estimate the cumulative incidence of breast cancer by baseline plasma RANKL and cox proportional hazards models were used to estimate the adjusted hazard ratios (HRs) and 95% confidence intervals (CI) for the association between plasma RANKL and risk. RESULTS: Over a mean follow-up of 6.3 years (0.02-19.24), 15 incident breast cancers were identified. The eight-year cumulative incidence was 10% in the low RANKL group and 12% in the high RANKL group (P-log-rank = 0.85). There was no significant association between plasma RANKL levels and breast cancer risk (multivariate HR high vs. low = 1.06; 95%CI 0.34-3.28; P-trend = 0.86). CONCLUSIONS: These findings suggest that circulating RANKL levels are not associated with breast cancer among BRCA mutation carriers. Pending validation in a larger sample, these findings suggest that RANKL is likely not a biomarker of breast cancer risk among BRCA mutation carriers.